Making spirits, making art, Nat carving and contemporary painting in pre-transition Myanmar (Burma) - Hasinoff, Erin L.; Kendall, Laurel (Material religion, 2018)
Embodiment, materiality, and technology intersect in the production of sacred images where tools, media, and intangible studio protocols inform the production of efficacious things. In Myanmar nat spirits appear in the bodies of costumed spirit mediums and in the intimately tended statues that adorn their altars. Prior to the recent democratic transition, nats appeared as the subjects of paintings, sometimes offering sociopolitical commentaries. This article explores the resonances between technologies of nat making in workshops that produce images for mediums and the techniques deployed by contemporary artists who have made nats the subjects of their paintings. In the Burmese religious world view, nats are lesser entities than the Buddha; their troubled histories of injustice account for their continuing agency as spirits in the human world. Appropriately, nat images are cruder than Buddha images; carvers are less likely to use precious wood or to observe Buddhist precepts and aesthetic guidelines while carving. A similar sense of the unrefined, unsettled nat is conveyed through the daring representational techniques and liberties of artists. We argue that connections between media, technique, and object agency can have resonance when sacred subjects are deployed in secular art.